2016
DOI: 10.1186/s13287-016-0350-z
|View full text |Cite
|
Sign up to set email alerts
|

Combined administration of mesenchymal stem cells overexpressing IGF-1 and HGF enhances neovascularization but moderately improves cardiac regeneration in a porcine model

Abstract: BackgroundInsulin-like growth factor 1 (IGF-1) and hepatocyte growth factor (HGF) are among the most promising growth factors for promoting cardiorepair. Here, we evaluated the combination of cell- and gene-based therapy using mesenchymal stem cells (MSC) genetically modified to overexpress IGF-1 or HGF to treat acute myocardial infarction (AMI) in a porcine model.MethodsPig MSC from adipose tissue (paMSC) were genetically modified for evaluation of different therapeutic strategies to improve AMI treatment. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 68 publications
1
38
0
Order By: Relevance
“…Since the porcine endogenous CSCs have an intact signalling IGF-1/HGF receptor system, the type of growth factor used in our investigation is considered as a good option for MI therapy 14 . Although the effects of administering different growth factors have been analysed in previous experiments 20 , to the best of our knowledge there are no studies that have examined the effect when delivered after its microencapsulation as a way to increase release time in a single intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Since the porcine endogenous CSCs have an intact signalling IGF-1/HGF receptor system, the type of growth factor used in our investigation is considered as a good option for MI therapy 14 . Although the effects of administering different growth factors have been analysed in previous experiments 20 , to the best of our knowledge there are no studies that have examined the effect when delivered after its microencapsulation as a way to increase release time in a single intervention.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that HGF prevented the progression of fibrogenesis in multiple organs such as lung, liver and heart (36,38,39). IGF1 exerts the beneficial effect on cardiac repair by enhancing angiogenesis and improving myocardial function (40). Previous studies demonstrated that SHH inhibited cardiac fibrosis, at least in part, by stimulating the production of paracrine factors that exert anti-fibrotic action (41).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, porcine models allow the opportunity to evaluate the therapeutic outcome with MRI, which is considered to provide the most accurate, comprehensive and reproducible measurements of cardiac chamber dimensions, volumes, function and infarct size compared with other techniques 8 . Unfortunately, in those studies on porcine and sheep models in which treatment success of cell-based therapies for (experimentally induced) MI was assessed using MRI, temporary occlusion of the left anterior descending (LAD) artery was (except of one study that showed no success 26 ) restricted to 60 min 27,28 or 90 min 29,30 . As a result, in most of these studies 27,28,30 the left ventricular ejection fraction (LVEF) after MI was between 42% and 54%, which may in clinical settings not represent the correct target population with moderate to severe left ventricular dysfunction 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, in those studies on porcine and sheep models in which treatment success of cell-based therapies for (experimentally induced) MI was assessed using MRI, temporary occlusion of the left anterior descending (LAD) artery was (except of one study that showed no success 26 ) restricted to 60 min 27,28 or 90 min 29,30 . As a result, in most of these studies 27,28,30 the left ventricular ejection fraction (LVEF) after MI was between 42% and 54%, which may in clinical settings not represent the correct target population with moderate to severe left ventricular dysfunction 8 . Furthermore, cells were delivered immediately after experimental induction of MI in twelve out of the 16 preclinical studies on cell-based therapy for MI using porcine and sheep animal models summarized in Supplementary Table 1.…”
Section: Introductionmentioning
confidence: 99%